PERCEPTION OF AMANAH ON MUSYARAKAH MUTANAQISAH FINANCING IN SHARIA BANKING IN GORONTALO (World Bulletin of Management and Law, 2022)
This study aims to understand and interpret the perception of trust in Musyarakah Mutanaqisah financing in Islamic banking in Gorontalo. In this study, the author uses a qualitative research method with an Islamic phenomenological approach and a new theory as the basis for discovering the perspective of trustworthiness on aqad musyarakah mutanaqisah in Islamic bank financial institutions in Gorontalo. Informants in this study were banks, customers and the Indonesian Ulema Council in Gorontalo The results of the study found the construction of the concept of trust on musyarakah mutanaqisah (MMQ) financing in Islamic banking in Gorontalo which contains values; 1. Policy; 2. Cooperation; 3. Transparency; 4. Accountability; 5. Trust; 6. Free from haram practices (maysir, gharar, usury). The basis for the fulfillment of the promise agreed in the musyarakah mutanaqisah contract is the trust in running a business that is entrusted to banks as third party fund managers as well as the mandate given by Islamic banks to financing customers. which prioritizes the aspect of trust in order to avoid the risks that will occur in Islamic banking institutions
Keywords: Musyarakah Mutanaqisah; Amanah; banking; Islamic